Community Radio as Amplification of Rural Knowledge Sharing. (December 2019) - Backhaus, Bridget
Community radio's relationship with the farming communities has a long history in India. The earliest successful experiments in community broadcasting involved both farmers and agriculture. In terms of development communication, community radio in India represents a confluence of somewhat conflicting paradigms. While community radio is generally presented as a highly democratic, participatory medium, the way it is operationalized in India more closely aligns with the modernization/diffusion paradigm. In 1976, Joseph Ascroft observed the phenomenon of 'interpersonal diffusion' among farmers, whereby for each farmer trained in new techniques, three more would adopt the innovations. While this 'interpersonal diffusion' was by no means perfect, it was illustrative of the complex communication networks involved in the diffusion process. It also hints towards the ways in which community radio can act as a facilitator of these processes; as somewhat of an intersection between diffusion and participatory communication. Drawing on ethnographically inspired qualitative research conducted at a rural community radio station in South India, this article explores the role of community radio at the intersections of participatory development and diffusion.  This article argues that community radio facilitates the sharing of technical information and innovations among farmers and contributes to amplifying existing knowledge communication systems. The implications of this article suggest that a focus on existing local knowledge communication and transfer systems could contribute to achieving broader development outcomes and further situating the role of community radio within development and social change initiatives.